2016
DOI: 10.1017/dmp.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Informal Networks in Disaster Medicine

Abstract: The results showed that informal networks promoted community-based ad hoc and formal networks, thus making overall disaster medicine and public health preparedness more effective. (Disaster Med Public Health Preparedness. 2017;11:343-354).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This could be attributed in part due to strong informal communication between organizations in the low-CPAT case, which can precipitate information sharing and referrals through informal mechanisms (e.g., ad-hoc communication, leveraging existing relationships to call colleagues in another organization to discuss a patient’s needs etc.) [ 73 74 75 ]. A higher degree of direct contact between network members, may have led organizations in low-CPAT led case to have greater awareness of the types of resources available in the Health Link, and thus directly coordinate care for patients through their frequent contact (possibly resulting in fewer referrals).…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed in part due to strong informal communication between organizations in the low-CPAT case, which can precipitate information sharing and referrals through informal mechanisms (e.g., ad-hoc communication, leveraging existing relationships to call colleagues in another organization to discuss a patient’s needs etc.) [ 73 74 75 ]. A higher degree of direct contact between network members, may have led organizations in low-CPAT led case to have greater awareness of the types of resources available in the Health Link, and thus directly coordinate care for patients through their frequent contact (possibly resulting in fewer referrals).…”
Section: Discussionmentioning
confidence: 99%
“…These networks are growing in critical situations where the need for cooperation is increasing. The application and usefulness of informal networks have been investigated in various studies (Bdeir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These networks are growing in critical situations where the need for cooperation is increasing. The application and usefulness of informal networks have been investigated in various studies (Bdeir et al, 2017). In fact, it can be said that the formal organization is like the skeleton of the organization, while the informal organization is the central nervous system (Krackhardt & Hanson, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear how the authors of previous work on this topic identified and coded coordination ties in formal documents. Moreover, informal networks have only been studied by a few scholars (e.g., Bdeir et al, 2017), and thus comprise an underresearched area of investigation. Network typologies should be developed to explicate the wide range of interactions among organizations participating in emergency management.…”
Section: Recommendations For Future Research and Practicementioning
confidence: 99%